Evaluation of hand circulation before radial forearm free flap surgery - Khan, Afroze S.; Henton, John M. D.; Adams, Titus S. T.; Dwivedi, Raghav C.; Harris, Paul A. (The Laryngoscope, 2009)
The radial forearm free flap (RFFF) is a versatile flap offering many reconstructive options for head and neck defects. Its low bulk, ease of dissection, and excellent vascularity are among its advantages. Its low flap loss and complication rates offer the best choice for the reconstruction of oral, oropharyngeal, and hypopharyngeal lining. Evaluation of collateral circulation to the hand is important to avoid distal ischemia and donor site morbidity. Pulse oximetry can be used to augment Allen's test to assess collateral supply to the hand. This cost‐neutral technique can be used in routine preoperative screening prior to RFFF surgery. Laryngoscope, 2009